Can Diabetes Mellitus Lead to Subclinical Vagal Neuropathy? A Prospective Clinical Study - Taskiran, Emine; Alkan, Zeynep; Adatepe, Turgut; Surmeli, Reyhan; Yigit, Ozgur; Yagiz, Orhan; Tanriverdi, Taner; Uzun Adatepe, Nurten (Cerrahpaşa Medical Journal, 2023)
Objective: Diabetic neuropathy is the most common chronic complication of diabetes mellitus. The vagal nerve and its branches might be affected, and the consequences can be very disastrous. This study aims to show if there is any subclinical vagal nerve involvement in diabetes mellitus. Methods: Fourteen patients with diabetic neuropathy without swallowing difficulty and dysphonia and 15 healthy controls were included in this prospective study. Nerve conduction studies, blink reflex, and swallowing studies were conducted. The results were compared between 2 groups. Results: Blink reflex exhibited abnormalities in patients compared to healthy controls. The recurrent laryngeal nerve motor response latency was significantly longer in patients (P < .001), whereas there was no significant difference for the pause period of swallowing. Conclusion: Prolonged distal motor latency of the recurrent laryngeal nerve in spite of normal swallowing pattern at the cricopharyngeal muscle electromyography in patients with diabetic neuropathy suggests subclinical vagal neuropathy and so lower cranial involvement. Patients should be informed about this clinical condition and closely followed up. Cite this article as: Taskiran, E, Alkan, Z, Adatepe, T, et al. Can diabetes mellitus lead to subclinical vagal neuropathy? A prospective clinical study. Cerrahpaşa Med J. 2023;47(3):243-246.